Personalism, persuasiveness, and engagement: a critical realist account of legitimacy and political support - Ostrowski, M (2012)
This thesis seeks to challenge the dominance of liberal accounts of legitimacy and support, and to remedy various faults it identifies in the literature with a rival account rooted in critical realism. Its overarching aim is to shift the focus away from ideal-theory hypotheses about what defines a 'perfect' structure, towards how agents think about and approach politics and ethics. It provides an overview of the status quo of liberal theorising about legitimacy and political support, followed by four methodological criticisms of the liberal approach: on the liberal treatment of agents with divergent views; the liberal conceptualisation of legitimacy; the blurring-together of legitimacy and political support; and political praxis concerns (part I). The thesis outlines a rival critical realist methodology to underpin its alternative account, emphasising the treatment of politics as a conflictual 'game', and a consequent focus on praxis criteria of success. It extends this discussion into a 'personalist' account of agents' political ontology, and the implications this has for a treatment of individual political agency that aspires to ecumenical appeal (II). On this basis, it outlines a procedural framework of legitimacy as persuasiveness that focuses on the way agents acquire, present, and exchange ethical and political beliefs in the political context. It defends this account against several possible liberal criticisms, and argues for its superiority on both theoretical and praxis grounds (III). Finally, it explores the implications of this conception for the ways in which agents dedicate themselves to obeying authority-structures, and for the connections of support that arise between agents and structures, highlighting the importance of continuous engagement to fully recognise the role of subjective agency in political decisions (IV).